2011
DOI: 10.1590/s1807-59322011000300014
|View full text |Cite
|
Sign up to set email alerts
|

Breast ultrasound diagnostic performance and outcomes for mass lesions using Breast Imaging Reporting and Data System category 0 mammogram

Abstract: PURPOSE:To evaluate the outcomes and diagnostic performance of ultrasonography after a Breast Imaging Reporting and Data System (Bi-RADS) category 0 mammogram.MATERIAL AND METHODS:This retrospective study reviewed 4,384 consecutive patients who underwent a screening mammography from January 2005 to July 2006; 391 of the 4,384 exams were classified as Bi-RADS category 0. After exclusions, 241 patients received subsequent sonogram. Ultrasonography was considered diagnostic when the Bi-RADS category was changed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…In the present study, all patients were from the Anhui Province, which is an undeveloped province in the middle of China, and most of these patients had dense breast tissue and small breast volume. Of the 274 cases, 38 (13.9%) were classified as BI-RADS category 0, meaning that an important proportion of women undergoing MG could not be satisfactorily assessed, which is supported by previous studies [ 19 , 20 ]. In addition, 30 (10.9%) patients assessed as being BI-RADS category 1 by MG had a palpable mass by clinical examination or had an obvious mass by US, prompting surgery.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the present study, all patients were from the Anhui Province, which is an undeveloped province in the middle of China, and most of these patients had dense breast tissue and small breast volume. Of the 274 cases, 38 (13.9%) were classified as BI-RADS category 0, meaning that an important proportion of women undergoing MG could not be satisfactorily assessed, which is supported by previous studies [ 19 , 20 ]. In addition, 30 (10.9%) patients assessed as being BI-RADS category 1 by MG had a palpable mass by clinical examination or had an obvious mass by US, prompting surgery.…”
Section: Discussionsupporting
confidence: 74%
“…Stratified analysis showed that young age, premenopausal, and high breast density decreased the diagnostic accuracy of MG. Indeed, dense breast tissues interfere with the interpretation of MG [ 5 , 20 - 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously examined the correlation between US findings and the corresponding histopathological features in breast disorders in our previous study (6). There have been relatively few reported studies on assessing US performance and its resolution without any mammographic abnormalities (8). Therefore, in this study, we evaluated US findings and the corresponding histopathological characteristics for breast cancer patients with Breast Imaging Reporting and Data System (BI-RADS) (9) category 1 mammogram.…”
Section: Introductionmentioning
confidence: 99%
“…Microcalcification was detected in 74% of patients with ductal carcinoma in situ of the breast (54 in 73 patients) [28]. Ultrasonography also detected abnormality when mammography reported Bi-RADS = 0 [29]. Subgroup analysis also showed that patients with Bi-RADS below 4 might gain more benefit from additional ultrasound investigation, while for those with Bi-RADS 4 and above who already had high possibility for cancer, ultrasound might not gain any additional information.…”
Section: Discussionmentioning
confidence: 99%